A Study Of Tacit Knowledge Management In The Public Sector - Gau, Wen-Bing (Journal of Knowledge Management Practice, 2011)
Some scholars have seen an organization as an entity that consists of lots of tangible and intangible knowledge. The concept of tangible and intangible knowledge echoes what Polanyi (1975) refers to as “tacit and explicit knowledge”. Some scholars such as Faulkner and Senker (1995) think that dividing knowledge into tacit and explicit types is inappropriate. They argue that people explain what they see and what they know in their own experiences. These experiences are usually in a tacit form. Therefore, even when people are delivering explicit information, they express both tacit and explicit knowledge.This research uses a qualitative method to explore the tacit way of knowledge management in the public sector in Taiwan. 11 public servants and 5 employees in the private sector were interviewed, while 3 departments in the central government and 2 departments in a privatized institution were visited. The researcher tries to explain how the individual and organizational learning are developed within the context of a bureaucratic organization. The theoretical dilemmas of Nonaka and Takeuchi’s (1995) views on knowledge management are discussed, such as the spiral of knowledge as well as the concept of redundancy. The ideological contradictions between the radical orientation of learning organization and knowledge management are also highlighted in this study.
Keywords: Knowledge management; Public sector; Tacit knowledge; Organizational learning